Produção de biocombustíveis a partir da hidrodesoxigenação de moléculas derivadas da pirólise da biomassa empregando Mo2C suportado - Machado, Marta Albuquerque (2018)
Catalytic performance of unsupported and supported molybdenum carbide (Mo2C) on oxide materials with different acid-base properties (Al2O3, ZrO2, e MgO) was evaluated in the deoxygenation of hydropyrolysis vapors of biomass using a pyrolyzergas chromatography/mass spectrometry system operated at 500 oC and 1 atm. The catalysts were synthesized by temperature programmed carburization. The samples were characterized by N2 physisorption at -196 °C, X ray diffraction, X ray fluorescence, inductively coupled plasma optical emission spectrometry, transmission electronic microscopy, NH3 adsorption, CO chemisorption and temperature programmed desorption of CO. Acidity of the support seems to play an important role in the deoxygenation of the vapors. While there was complete removal of oxygen when Mo2C/Al2O3 and Mo2C/ZrO2 were used, the same did not take place for the more basic catalyst: Mo2C/MgO. A large amount of carbonyl compounds was formed in non-catalytic hydropyrolysis. For this reason, vapor-phase hydrodeoxygenation reaction was studied using acetone as model molecule in order to investigate the reaction routes involved and, therefore, to determine the effect of the support with this model reaction. The tests were carried out at 200 oC and 1 atm, and showed that the unsupported Mo2C was more active and more selective to propene and propane, which are the final products of the acetone hydrodeoxygenation. The supported carbides promoted the formation of compounds derived from the acetone condensation reaction. All catalysts showed deactivation due to deposition of polymeric carbon probably on the Lewis acid sites and on basic sites.